Light limitation inducing overcompensatory growth of cyanobacteria and function of serine/threonine kinase (STK) genes involved - Chen, Gao; Bi, Xiangdong; Zhong, Huairong; Wang, Xueying; Dong, Shaojie; Lv, Dong; Zhang, Shulin; Zhang, Dajuan; Wang, Na (Water science and technology : a journal of the International Association on Water Pollution Research, 2021)
The rapid overcompensatory growth that appears when cyanobacteria are supplied with adequate resources after a period of resource deprivation might contribute to the occurrence of cyanobacterial blooms. We investigated the changing characteristics of overcompensatory growth and serine/threonine kinase (STK) genes expression of cyanobacterium Microcystis aeruginosa in response to light limitation. The results showed M. aeruginosa exhibited overcompensatory growth for 2 days after light recovery, during which the increase in growth was inversely related to light intensity. Expression of STK genes, such as spkD, was upregulated significantly at 0.5-4 h after light recovery (P < 0.05). To investigate the function of STK genes in the overcompensatory growth, M. aeruginosa spkD was heterologously expressed in Synechocystis. Transgenic Synechocystis exhibited greater and longer overcompensatory growth than wild-type Synechocystis after light recovery. Relative expression levels of STK genes in transgenic Synechocystis were significantly higher than those in wild-type Synechocystis at 24 h of light recovery (P < 0.05). Heterologous expression of Microcystis spkD might stimulate overcompensatory growth of Synechocystis by affecting its STK gene expression